Genome-wide association scan and transcriptome analysis reveal candidate genes for waterlogging tolerance in cultivated barley - Luan, Haiye; Chen, Changyu; Yang, Ju; Qiao, Hailong; Li, Hongtao; Li, Shufeng; Zheng, Junyi; Shen, Huiquan; Xu, Xiao; Wang, Jun (Frontiers in Plant Science, 2022)
Waterlogging is the primary abiotic factor that destabilizes the yield and quality of barley (Hordeum vulgare L.). However, the genetic basis of waterlogging tolerance remains poorly understood. In this study, we conducted a genome-wide association study (GWAS) by involving 106,131 single-nucleotide polymorphisms (SNPs) with a waterlogging score (WLS) of 250 barley accessions in two years. Out of 72 SNPs that were found to be associated with WLS, 34 were detected in at least two environments. We further performed the transcriptome analysis in root samples from TX9425 (waterlogging tolerant) and Franklin (waterlogging sensitive), resulting in the identification of 5,693 and 8,462 differentially expressed genes (DEGs) in these genotypes, respectively. The identified DEGs included various transcription factor (TF) genes, primarily including AP2/ERF, bZIP and MYB. By combining GWAS and RNA-seq, we identified 27 candidate genes associated with waterlogging, of which three TFs (HvDnaJ, HvMADS and HvERF1) were detected in multiple treatments. Moreover, by overexpressing barley HvERF1 in Arabidopsis, the transgenic lines were detected with enhanced waterlogging tolerance. Altogether, our results provide new insights into the genetic mechanisms of waterlogging, which have implications in the molecular breeding of waterlogging-tolerant barley varieties.